2017
DOI: 10.1038/s41523-017-0016-8
|View full text |Cite
|
Sign up to set email alerts
|

Dual PI3K and Wnt pathway inhibition is a synergistic combination against triple negative breast cancer

Abstract: Triple negative breast cancer accounts for 15–20% of all breast cancer cases, but despite its lower incidence, contributes to a disproportionately higher rate of mortality. As there are currently no Food and Drug Administration-approved targeted agents for triple negative breast cancer, we embarked on a genomic-guided effort to identify novel targeted modalities. Analyses by our group and The Cancer Genome Atlas have identified activation of the PI3K-pathway in the majority of triple negative breast cancers. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 40 publications
(38 reference statements)
0
29
0
Order By: Relevance
“…PI3K inhibition promotes the expression of Wnt ligands in breast cancers, whereas BRAF inhibition upregulates b-catenin signaling through activating the focal adhesion kinase in colorectal cancer. Blocking Wnt/b-catenin signaling by tankyrase inhibitor or PORCN inhibitor can significantly enhance the tumor suppression effect of these small molecular inhibitors targeting the growth factor signaling pathways (Tzeng et al, 2015;Solzak et al, 2017;Chen et al, 2018;Solberg et al, 2018). In EGFRmutated lung cancer, even though EGFR inhibitors are not observed to significantly upregulate Wnt signaling in preclinical studies, Wnt/b-catenin signaling has been shown to drive resistance to EGFR inhibitors in lung cancer cells because tankyrase inhibitor and EGFR inhibitor in combination can synergistically suppress lung cancer cell growth in vitro and in vivo (Casás-Selves et al, 2012;Scarborough et al, 2017).…”
Section: Downloaded Frommentioning
confidence: 99%
“…PI3K inhibition promotes the expression of Wnt ligands in breast cancers, whereas BRAF inhibition upregulates b-catenin signaling through activating the focal adhesion kinase in colorectal cancer. Blocking Wnt/b-catenin signaling by tankyrase inhibitor or PORCN inhibitor can significantly enhance the tumor suppression effect of these small molecular inhibitors targeting the growth factor signaling pathways (Tzeng et al, 2015;Solzak et al, 2017;Chen et al, 2018;Solberg et al, 2018). In EGFRmutated lung cancer, even though EGFR inhibitors are not observed to significantly upregulate Wnt signaling in preclinical studies, Wnt/b-catenin signaling has been shown to drive resistance to EGFR inhibitors in lung cancer cells because tankyrase inhibitor and EGFR inhibitor in combination can synergistically suppress lung cancer cell growth in vitro and in vivo (Casás-Selves et al, 2012;Scarborough et al, 2017).…”
Section: Downloaded Frommentioning
confidence: 99%
“…We next used publicly available cancer transcriptome data set (as described by Solzak et al 44 ) to determine whether the genes targeted by the combination treatments (DEGs) are known to be differentially expressed in triple‐negative breast cancer patients and therefore potentially important for the cancer state. Although the overlap between the genes which were up‐regulated by SAM + 5AzadC but down‐regulated in patients was not significant as determined by a hypergeometric test (Figure 4C), there was a significant overlap of 71 genes which were down‐regulated by SAM + 5AzadC treatment with the set of genes which were up‐regulated in breast cancer patients (hypergeometric test, P < 0.05) (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…SRI35889 and to a lesser extent, SRI33576, were found to inhibit mTOR signaling in addition to Wnt/β-catenin activity, which may confer increased cytotoxic potency in TNBC. Recently, a study supported the use of dual inhibition of both PI3K/AKT/mTOR and Wnt/β-catenin pathways for synergistic effects in TNBC [ 70 ]. Interestingly, treatment of TNBC with the pan-PI3K inhibitor buparlisib increased Wnt/β-catenin activity via increased expression of Wnt/β-catenin pathway mediators such as FZDs, Wnt ligands, LRP4/6 and porcupine.…”
Section: Discussionmentioning
confidence: 99%